EFEKTIVITAS E-LKPD BERBASIS PBL UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK PADA MATERI KEANEKARAGAMAN HAYATI - Dewi, Nurlita Ariyani Benita; Rahayu, Yuni Sri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The education system is required to adapt to technological advancements. The demands of 21st-century competencies also emphasize the importance of having 4C skills (Communication, Collaboration, Critical Thinking, Creativity). One of the skills that needs special attention is critical thinking skills. The results of the 2022 PISA survey show that Indonesia's PISA scores have declined compared to 2018. The improvement of critical thinking skills is supported by the use of an appropriate learning model, namely Problem Based Learning. This research aims to produce PBL-based E-LKPD on biodiversity material to enhance students' critical thinking skills, which is deemed effective. The development was carried out using the ADDIE model (analyze, design, development, implementation, evaluation). E-LKPD was tested on a limited basis with 36 tenth-grade students from SMA Negeri 9 Surabaya. Data were obtained through the results of pre-tests and post-tests based on five critical thinking indicators, which were then analyzed descriptively and quantitatively. The five critical thinking indicators practiced in the E-LKPD, pre-test, and post-test include interpretation, analysis, evaluation, inference, and explanation. The results of the study showed that the effectiveness of E-LKPD obtained an n-gain score of 0.92, which is included in the high improvement category, so that PBL-based E-LKPD is considered effective in improving students' critical thinking skills.